A sensitive and efficient trifluoroacetyl-based aromatic fluorescent probe for organic amine vapour detection1. Issue 32 (10th April 2015) - Yao, Junjun; Fu, Yanyan; Xu, Wei; Fan, Tianchi; He, Qingguo; Zhu, Defeng; Cao, Huimin; Cheng, Jiangong
<x xml:space="preserve">Abstract</x> Highly reversible, sensitive and efficient trifluoroacetyl-substituted fluorescent probes were designed for discriminating multiple trace organic amine vapours.